Effect of Boron Element Additions on Microstructure, Biocompatibility, and Thermodynamic Parameters of NiTi Shape Memory Alloy - Qader, Ibrahim Nazem; Ercan, Ercan; Orhan, Ayhan (Springer, 2022)
In this study, the thermodynamic and microstructural effects of boron element on a Ni-riched NiTi shape memory alloy (SMA) were investigated and the biocompatibility of the improved alloy was compared with the binary alloy. X-ray diffraction measurements showed that at room temperature the binary NiTi SMA was in the austenite (B2) phase, which was also supported by differential scanning calorimetry (DSC) measurements. When the NiTi alloy was doped with a low concentration of B, new phases appeared, e.g., SEMEDX analyses of NiTiB alloy reveal the presence of Ni3Ti phase structure and beta-Ti and Ni-rich matrix structures. Boron additive decreased the DSC peaks of martensitic phase transformation (B2 <-> B19') of the NiTi alloy; therefore, all thermomechanical parameters investigated in this study were affected. On the other hand, it was determined that although the amount of Ni leakage in both alloys conform to the standards, the biocompatibility of NiTi alloy was improved by adding only 0.8 at% B, which reduced Ni ion release.
Keywords: Martensitic-Transformation; Mechanical-Properties; Phase-Transformation; Behavior; Temperature; Energy; Superelasticity; Precipitation; Dependence